A history of baseball in 100 objects : a tour through the bats, balls, uniforms, awards, documents, and other artifacts that tell the story of the national pastime /: a tour through the bats, balls, uniforms, awards, documents, and other artifacts that tell the story of the national pastime. ([2015]) - Leventhal, Josh, 1971-
No abstract available